Caesarean section and severe upper and lower respiratory tract infections during infancy: evidence from two UK cohorts - Alterman, N; Kurinczuk, JJ; Quigley, MA (Public Library of Science, 2021)
Background Several studies have reported that birth by caesarean section is associated with increased risk of lower respiratory tract infections in the child, but it is unclear whether this applies to any caesarean section or specifically to planned caesareans. Furthermore, although infections of the upper respiratory tract are very common during childhood, there is a scarcity of studies examining whether caesarean is also a risk factor for this site of infection. Methods We obtained data from two UK cohorts: the Millennium Cohort Study (MCS) and linked administrative datasets of the population of Wales through the Secure Anonymised Information Linkage (SAIL) databank. The study focused on term-born singleton infants and included 15,580 infants born 2000–2002 (MCS) and 392,145 infants born 2002–2016 (SAIL). We used information about mode of birth (vaginal delivery, assisted vaginal delivery, planned caesarean and emergency caesarean) from maternal report in the MCS and from hospital birth records in SAIL. Unplanned hospital admission for lower respiratory tract infection (LRTI) was ascertained from maternal report in the MCS and from hospital record ICD codes in SAIL. Information about admissions for upper respiratory tract infection (URTI) was available from SAIL only. Cox regression was used to estimate hazard ratios for each outcome and cohort separately while accounting for a wide range of confounders. Gestational age at birth was further examined as a potential added, indirect risk of planned caesarean birth due to the early delivery. Findings The rate of hospital admission for LRTI was 4.6 per 100 child years in the MCS and 5.9 per 100 child years in SAIL. Emergency caesarean was not associated with LRTI admission during infancy in either cohort. In the MCS, planned caesarean was associated with a hazard ratio of 1.39 (95% CI 1.03, 1.87) which further increased to 1.65 (95% CI 1.24, 2.19) when gestational age was not adjusted for. In SAIL, the adjusted hazard ratio was 1.10 (95% CI 1.05, 1.15), which increased to 1.17 (95% CI 1.12, 1.22) when gestational age was not adjusted for. The rate of hospital admission for URTI was 5.9 per 100 child years in SAIL. Following adjustments, emergency caesarean was found to have a hazard ratio of 1.09 (95% CI 1.05, 1.14) for hospital admission for URTI. Planned caesarean was associated with a hazard ratio of 1.11 (95% CI 1.06, 1.16) which increased to 1.17 (95% CI 1.12, 1.22) when gestational age was not adjusted for. Conclusions The risk of severe LRTIs during infancy is moderately elevated in infants born by planned caesarean compared to those born vaginally. Infants born by any type of caesarean may also be at a small increased risk of severe URTIs. The estimated effect sizes are stronger if including the indirect effect arising from planning the caesarean birth for an earlier gestation than would have occurred spontaneously. Further studies are needed to confirm these results.